2006
DOI: 10.1021/tx050240y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pectenotoxin-11 as 34S-Hydroxypectenotoxin-2, a New Pectenotoxin Analogue in the Toxic Dinoflagellate Dinophysis acuta from New Zealand

Abstract: A new pectenotoxin, which has been named pectenotoxin-11 (PTX11), was isolated from the dinoflagellate Dinophysis acuta collected from the west coast of New Zealand. The structure of PTX11 was determined as 34S-hydroxypectenotoxin-2 by tandem mass spectrometry and UV and NMR spectroscopy. PTX11 appears to be only the third pectenotoxin identified as a natural biosynthetic product from algae after pectenotoxin-2 and pectenotoxin-12. The LD50 of PTX11 determined by mouse intraperitoneal injection was 244 microg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 24 publications
0
60
1
Order By: Relevance
“…Pectenotoxin-11 has been reported from New Zealand (Suzuki et al, 2003), the Galician Rías, Spain (Pizarro et al, 2008), North Sea (Krock et al, 2008), along the Chilean coast (Blanco et al, 2007;Krock et al, 2009;Trefault et al, 2011) and from the Benguela Current, South Africa (Pitcher et al, 2011), but this is the first report for the Argentinean Sea. Although this toxin was already associated with Dinophysis acuta (MacKenzie et al, 2005;Suzuki et al, 2006) and Dinophysis acuminata (MacKenzie et al, 2005), our data do not strongly support Dinophysis tripos being a producer of PTX-11, because there was little correlation between the toxin and the species (r = 0.67). A possible explanation for this low correlation is that D. tripos might feed on the original producer of the toxin which could be D. acuminata, as it was present in some stations.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Pectenotoxin-11 has been reported from New Zealand (Suzuki et al, 2003), the Galician Rías, Spain (Pizarro et al, 2008), North Sea (Krock et al, 2008), along the Chilean coast (Blanco et al, 2007;Krock et al, 2009;Trefault et al, 2011) and from the Benguela Current, South Africa (Pitcher et al, 2011), but this is the first report for the Argentinean Sea. Although this toxin was already associated with Dinophysis acuta (MacKenzie et al, 2005;Suzuki et al, 2006) and Dinophysis acuminata (MacKenzie et al, 2005), our data do not strongly support Dinophysis tripos being a producer of PTX-11, because there was little correlation between the toxin and the species (r = 0.67). A possible explanation for this low correlation is that D. tripos might feed on the original producer of the toxin which could be D. acuminata, as it was present in some stations.…”
Section: Discussioncontrasting
confidence: 83%
“…This relation between PTX-2sa and Dinophysis spp. (8.16 pg cell À1 ) was previously reported for natural plankton food suspensions rich in Dinophysis norvegica cells (Kozlowsky- Suzuki et al, 2006). However, additional field studies as well as culture establishment are required to unambiguously elucidate the toxin profile of this species and the possible production of PTX-2sa by this genus, as well as to test its bioaccumulation in the food web.…”
mentioning
confidence: 75%
“…52 Both compounds showed many common fragment ions, but a few of the ions were shifted up or down in mass by 16 amu. Figure 13 presents a proposed assignment of fragment ions deduced from examination of the structure and through comparison of the spectra of PTX1 and PTX11.…”
Section: Lc-ms/ms Spectra For [M+nh4]mentioning
confidence: 98%
“…PTX2 has been reported to be present in the toxic dinoflagellates Dinophysis spp., [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] which is also the causative species of OA and DTXs. Recently, several novel pectenotoxins, PTX11, 45,52 PTX12, 46 PTX13, 53 and PTX14, 53 were found in Dinophysis spp. by using LC-MS.…”
Section: 3mentioning
confidence: 99%
“…Although these toxins were initially classified in the DSP group, their diarrheic toxicity to humans has not been proven. Actually, it has been recently demonstrated that oral administration to mice does not cause any toxic effect, in spite of the toxicity induced by intraperitoneal administration [52,53]. The mechanism of action of pectenotoxin seems related to the disruption of the actin cytoskeleton observed in vitro [54][55][56][57].…”
Section: Pectenotoxinsmentioning
confidence: 99%